GUARDIANS OF TRUST: An Artificial Intelligence-BlockChain-Biometric Framework for Immutable Document Authentication in Kenya's Digital Economy - Charles Ochieng' Oguk,; Jane Juma, (IJRDO -Journal of Computer Science Engineering, 2025)
Document fraud poses a pervasive and debilitating threat across Kenya's socio-economic sectors, undermining vital processes like financial inclusion, education, land tenure, trade and employment, among others. Current manual or rudimentary semi-digital authentication methods, such as ink stamps and physical checks, are insufficient and highly susceptible to sophisticated forgery. These approaches often fail to comprehensively verify identity, creating critical vulnerabilities in trust and accountability within the evolving digital economy. This paper proposes and develops a novel AI-Blockchain-Biometric Framework for immutable and verifiable document authentication across Kenya's diverse digital economic landscape. The framework synergistically integrates distributed ledger technology (blockchain) for unparalleled data immutability, transparency, and integrity; advanced Artificial Intelligence (AI) for robust anomaly detection, liveness verification, and sophisticated pattern recognition; and multi-modal biometrics (like facial recognition, fingerprint) for secure, comprehensive identity verification of the document holder. This multi-factor approach significantly enhances authentication robustness. The anticipated impact is a significant reduction in fraud, fostering enhanced trust, and vastly improving efficiency in official processes across government, finance, and employment sectors in Kenya. This ultimately strengthens Kenya's broader digital economy by ensuring the authenticity and integrity of critical information. This research utilizes a mixed-methods approach, detailing the conceptual and architectural design of the framework, informed by a comprehensive literature review, examination of current practices, simulation and qualitative data gathering to establish system requirements and validate efficacy.